2015
DOI: 10.1186/s40064-015-1588-0
|View full text |Cite
|
Sign up to set email alerts
|

STOP-BANG questionnaire as a screening tool for diagnosis of obstructive sleep apnea by unattended portable monitoring sleep study

Abstract: The Snoring, Tiredness, Observed apnea, high blood Pressure (STOP)-Body mass index (BMI), Age, Neck circumference, and Gender (BANG) questionnaire is a well validated screening tool for diagnosis of Obstructive sleep apnea (OSA) by an in- lab sleep study. However, performance of STOP-BANG as a screening tool for diagnosis of OSA in patients undergoing portable monitoring (PM) sleep study has not been well validated. We conducted a retrospective chart review of patients older than 18 years who had unattended po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…The STOP-BANG questionnaire was recently compared and validated against traditional diagnostic sleep studies, which demonstrated that higher STOP-BANG scores had a specificity and positive predictive value as high as 98.3% and 98.5%, respectively, in diagnosing OSA when compared with the gold standard, PSG. 18…”
Section: Methodsmentioning
confidence: 99%
“…The STOP-BANG questionnaire was recently compared and validated against traditional diagnostic sleep studies, which demonstrated that higher STOP-BANG scores had a specificity and positive predictive value as high as 98.3% and 98.5%, respectively, in diagnosing OSA when compared with the gold standard, PSG. 18…”
Section: Methodsmentioning
confidence: 99%
“…The STOP-BANG questionnaire was administered to all patients. 30 For those with a previous diagnosis of OSA who were treated with CPAP, objective measures of CPAP use were recorded. Intraoperative data included type of anesthetic, surgical duration, airway management, medications including type and amount of opioid use converted to parenteral morphine equivalents (PME), and notation of the following adverse events: direct laryngoscopy attempts, intubating grade, and airway management changes due to adverse conditions.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Nevertheless, the findings of this study need to be interpreted within the context of several limitations. First, while the STOP-Bang Questionnaire is a widely accepted, validated, and reliable measure of OSA that is often used in sleep research, 41 and as a diagnostic tool, 42 it is not as robust as an overnight polysomnography for calculation of apnea-hypopnea index. Indeed, the STOP-bang questionnaire has high sensitivity but low specificity with low scores, which constitutes the majority of our population sample.…”
Section: Discussionmentioning
confidence: 99%